The Influence of Education Costs on Economics Learning Outcomes of High School Students - Cici Apriani Majid (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This study aims to determine the effect of educational costs incurred by parents on the learning outcomes of class X students at SMA Negeri 2 Watansoppeng Methodology: The independent variable (independent variable) in this study is the cost of education as the X variable, while the dependent variable (the devenden variable) is the Learning Outcome as the Y variable. The population in this study is all students of class X.2 at SMA Negeri 2 Watansoppeng Academic Year 2015/2016, which totaled 177 students. The number of students who were sampled in this study were 28 students using the Simple Random Sampling technique. The data collection technique used was a list of questions. The data analysis technique used is descriptive quantitative analysis technique (descriptive statistics) used to describe the variable costs of education and learning outcomes variables, simple linear regression is used to determine the effect of the independent variable on the dependent variable, the F test is used to test the research hypothesis, the coefficient of determination is used to determine the contribution of independent variables to dependent variables Main Findings: The cost of education has a positive effect on the learning outcomes of class X students at SMA Negeri 2 Watansoppeng Novelty/Originality of this research: As material for evaluating the effect of educational costs incurred by parents on student learning outcomes.